Beyond the Synagogue: Jewish Nostalgia as Religious Practice, by RACHEL B. GROSSCultural Disjunctions: Post-Traditional Jewish Identity, by PAUL MENDES-FLOHR - Caplan, Jennifer (Sociology of religion, 2022)
It might have come as a surprise to Thomas Morgan, the author of the now infamous Look magazine cover story “The Vanishing American Jew” (May 5, 1964) that, as